2019
DOI: 10.21203/rs.2.12696/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Drivers of Antibiotic Use and Misuse: The Development and Investigation of a Theory Driven Community Measure

Abstract: Background: Antimicrobial resistance is a global public health concern, with extensive associated health and economic implications. Actions to slow and contain the development of resistance are imperative. Despite the fact that overuse and misuse of antibiotics are highlighted as major contributing factors to this resistance, no sufficiently validated measures aiming to investigate the drivers behind consumer behaviour amongst the general population are available. The objective of this study was to develop and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…In this study, it was found that most of the human healthcare students were males and within the age group of 21 -25 years with the majority of them in 400 Level. These findings coincide with previous studies on knowledge and practices in the use of antibiotics among a group of Nigerian university students [14].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, it was found that most of the human healthcare students were males and within the age group of 21 -25 years with the majority of them in 400 Level. These findings coincide with previous studies on knowledge and practices in the use of antibiotics among a group of Nigerian university students [14].…”
Section: Discussionsupporting
confidence: 91%
“…One of the main drivers behind the development of AMR is the misuse and overuse of antibacterial agents [ 18 , 19 ]. As the utilisation of antibacterials can be controlled [ 20 ], rationalization of use is of pivotal importance to curb AMR. Emergency care departments (EDs) are unique in the health care system, providing an interface between ambulatory care and hospital care settings [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, antibiotics are often believed to be “wonder drugs” with the ability to cure any ailment. Such attitudes greatly influence the irrational use of antibiotics in the community [ 3 , 6 ]. Lack of knowledge about the activity of antibiotics on bacteria and in the inactivity of antibiotics on other pathogens (such as viruses, fungi and parasites), and about the emergence of antibiotic resistance in case of inappropriate antibiotic use, also influence irrational use [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%